Xenobiotic-Metabolizing Gene Polymorphisms and Ovarian Cancer Risk - Goode, Ellen L. (2010)
Because selected xenobiotic-metabolizing enzymes process pro-carcinogens that could initiate ovarian carcinogenesis, we hypothesized that single-nucleotide polymorphisms (SNPs) in the genes encoding xenobiotic-metabolizing enzymes are associated with risk of ovarian cancer. Cases with invasive epithelial ovarian cancer (N = 1,571 including 956 of serous sub-type) and controls (N = 2,046) from three studies were genotyped at 11 SNPs in EPHX1, ADH4, ADH1A, NQO2, NAT2, GSTP1, CYP1A1, and NQO1, following an initial SNP screen in a subset of participants. Logistic regression analysis of genotypes obtained via Illumina GoldenGate and Sequenom iPlex technologies revealed the following age- and study-adjusted associations: EPHX1 rs1051740 with increased serous ovarian cancer risk (per-allele odds ratio (OR) 1.17, 95% confidence interval (95% CI) 1.04–1.32, p = 0.01), ADH4 r1042364 with decreased ovarian cancer risk (OR 0.90, 95% CI 0.81–1.00, p = 0.05), and NQO1 rs291766 with increased ovarian cancer risk (OR 1.11, 95% CI 1.00–1.23, p = 0.04). These findings are consistent with prior studies implicating these genes in carcinogenesis and suggest that this collection of variants is worthy of follow-up in additional studies.